2021
DOI: 10.3390/app11209405
|View full text |Cite
|
Sign up to set email alerts
|

The Human Meniscus Behaves as a Functionally Graded Fractional Porous Medium under Confined Compression Conditions

Abstract: In this study, we observe that the poromechanical parameters in human meniscus vary spatially throughout the tissue. The response is anisotropic and the porosity is functionally graded. To draw these conclusions, we measured the anisotropic permeability and the “aggregate modulus” of the tissue, i.e., the stiffness of the material at equilibrium, after the interstitial fluid has ceased flowing. We estimated those parameters within the central portion of the meniscus in three directions (i.e., vertical, radial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…Whereas the internal layer of the meniscus relies on a hierarchical anisotropic network of collagen channels mainly aligned along the circumferential direction in which fluid flows during the physiological deformation process (Figure 1). In [5], we have shown that the permeability changes from the anterior/posterior horns to the body region, with the body region being more permeable. Here, we show that the permeability tensor in this region is also transversely isotropic and that the permeability in the circumferential direction (the preferential direction of the collagen channel) is higher than the other two directions (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Whereas the internal layer of the meniscus relies on a hierarchical anisotropic network of collagen channels mainly aligned along the circumferential direction in which fluid flows during the physiological deformation process (Figure 1). In [5], we have shown that the permeability changes from the anterior/posterior horns to the body region, with the body region being more permeable. Here, we show that the permeability tensor in this region is also transversely isotropic and that the permeability in the circumferential direction (the preferential direction of the collagen channel) is higher than the other two directions (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
“…Biological soft tissues, such as the meniscal tissue (Figure 1), exhibit a hierarchical porous solid matrix and an interstitial fluid flowing into the pores [1][2][3][4][5]. The overall mechanical behaviour depends not only on the solid matrix deformation but also on the movement of the fluid in and out of the pores during the deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To describe this type of porous-media behaviour, Barrera's group introduced Caputo fractional derivatives into Darcy's law, and implemented this fractional pore pressure diffusion equation in ABAQUS (Barrera 2021). This modelling scheme was then adopted to successfully predict the human meniscus behaviour under confined compression conditions against experiments (Bulle et al 2021). However, these methodologies most often adopted poroelastic theory, and thus integrating the solid and fluid phases in a continuum model (Jamal et al 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…For example, size-effects within lowdimensional (micro-and nano-scale) structures, such as carbon nanotubes, emerge due to the long-range forces that become more prevalent at these scales [5,6]. Several studies have also demonstrated the presence of nonlocal interactions at the macro-scale in complex structures like porous solids [7][8][9], periodic structures [10,11], intentionally engineered nonlocal structures [12], and sandwiched structures [13]. The inability of the classical (local) continuum theory to capture the nonlocal effects has been one of the main drivers fostering the development of nonlocal continuum theories.…”
Section: Introductionmentioning
confidence: 99%